Metal nanocluster and preparation method and application thereof

By introducing water molecules into metal nanoclusters, forming metal oxygen bonds and hydrogen bonds, defective luminescence is suppressed, intrinsic luminescence is promoted, and the intrinsic luminescence performance adjustment is solved in the prior art, and efficient luminescence performance improvement and adjustable luminescence color are achieved.

CN119910176AActive Publication Date: 2025-05-02JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510103692.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art has shortcomings in regulating structural defects of metal nanoclusters and improving their luminescence properties, especially how to improve photoluminescence quantum yield (PLQY) by adjusting surface defect chemistry and electron relaxation kinetics has not been fully studied.

Method used

By introducing water molecules into metal nanoclusters and forming metal oxygen bonds with exposed metal atoms, defective state luminescence caused by structural oxygen vacancies is inhibited, and the dominant role of cluster intrinsic state luminescence is promoted, thereby increasing the radiation rate. At the same time, the introduction of water molecules enhances the stability of metal nanoclusters through hydrogen bonding, inhibiting non-radiation loss and electron-optical phonon coupling.

Benefits of technology

The luminescence quantum efficiency of metal nanoclusters was significantly improved, from 5.3% defective state luminescence to 91.6% intrinsic state luminescence, and the luminescence color was adjusted in the millisecond level, rapidly adjusting from 536nm to 480nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910176A_ABST
    Figure CN119910176A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides a metal nanocluster and a preparation method and application thereof.The preparation method of the metal nanocluster comprises the steps that a metal salt aqueous solution is added into ultrapure water, after uniform stirring, a 3-mercaptopropionic acid solution is added, the mixture continues to be stirred for a reaction till sediment is generated, and a metal nanocluster solution is obtained; adjusting the pH value of the solution to 7.70-8.40, then adding a zinc salt aqueous solution, and carrying out a reaction under an ultraviolet irradiation condition to induce self-assembly of the metal nanoclusters; and adding a zinc salt aqueous solution into the obtained metal nanocluster, carrying out a stirring reaction, carrying out centrifugation, discarding a supernatant, carrying out freeze-drying treatment, and exposing the metal nanocluster subjected to freeze-drying treatment in an environment with a relative humidity of not less than 2% so as to enable water molecules to interact with metal oxygen bonds through hydrogen bonds. Structural oxygen vacancy defects in the metal nanoclusters are passivated through water molecules, the light-emitting quantum efficiency of the metal nanoclusters is remarkably improved, and rapid color regulation and control are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a metal nanocluster and a preparation method and application thereof. Background Art

[0002] Structural defects play an important role in regulating the optical and electronic properties of materials, especially in multiple application fields such as energy storage, catalysis, photovoltaics, and optoelectronics. Defects usually include vacancies, interstitial atoms, and substitutional impurities, which are generated during synthesis, purification, modification, storage, and application. Especially in luminescent materials, structural defects often introduce intermediate energy levels, affecting the transmission path of electrons and the relaxation process of excited state electrons, thereby affecting photoluminescence (PL) performance. Therefore, the controlled introduction of structural defects has become an important means to regulate the optical properties of materials.

[0003] Metal nanoclusters (NCs) show a strong dependence on structural defects due to their ultra-small size (usually less than 3 nm) and abundant dangling bonds or exposed surfaces. The high crystal index, topological complexity and interaction of metal nanoclusters with ligands promote the formation of structural defects. In recent years, surface metal vacancies and point defects in metal nanoclusters have been discovered, and these structural defects play a key role in regulating the optical and electronic properties of metal nanoclusters. However, the current research on structural defects in metal nanoclusters is still insufficient, mainly manifested in: on the one hand, the formation of structural defects will reduce the stability of metal nanoclusters, resulting in their characterization only in single crystals or solutions; on the other hand, the research on optimizing PL performance by passivating structural defects is relatively limited, especially how to improve PL quantum yield (PLQY) by adjusting surface defect chemistry and electron relaxation dynamics has not been fully studied.

[0004] Therefore, developing a method that can effectively regulate the structural defects of metal nanoclusters and significantly improve their luminescence performance, especially improving PLQY and adjusting the luminescence color, has become an important topic in this field. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a method for preparing metal nanoclusters, aiming to develop a method that can effectively regulate the structural defects of metal nanoclusters and significantly improve their luminescence performance.

[0006] The embodiment of the present application is implemented as follows: a method for preparing metal nanoclusters, characterized by comprising:

[0007] Adding a metal salt aqueous solution to ultrapure water, stirring evenly, then adding a 3-mercaptopropionic acid solution and continuing to stir and react until precipitation is generated, adjusting the pH value of the solution to 7.70-8.40, then adding a zinc salt aqueous solution, and reacting under ultraviolet light irradiation to induce self-assembly of metal nanoclusters;

[0008] A zinc salt aqueous solution is added to the obtained metal nanoclusters for stirring reaction, and after centrifugation and discarding the supernatant, freeze-drying is performed, and the freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds, thereby obtaining;

[0009] Wherein, the metal salt aqueous solution is a chloroauric acid aqueous solution or a mixture of a chloroauric acid aqueous solution and a silver nitrate aqueous solution or a cupric chloride aqueous solution.

[0010] The embodiment of the present application further provides a metal nanocluster, which is prepared by the above-mentioned method for preparing the metal nanocluster.

[0011] The embodiments of the present application also provide an application of the above-mentioned metal nanoclusters in the fields of optoelectronic devices, sensors, and photocatalysts.

[0012] The embodiment of the present application introduces water molecules into metal nanoclusters to form metal oxygen bonds with exposed metal atoms, thereby suppressing the defect state luminescence caused by structural oxygen vacancies and promoting the dominant role of cluster intrinsic state luminescence, thereby increasing the radiation rate; in addition, the introduction of water molecules also enhances the stability of metal nanoclusters through hydrogen bonds, suppresses non-radiative losses, and reduces electron-optical phonon coupling. Through the method of the present application, the quantum efficiency of metal nanoclusters is significantly improved from 5.3% (defect state luminescence) to 91.6% (intrinsic state luminescence), and the luminescent color can be adjusted within milliseconds, quickly adjusted from 536nm to 480nm, which has important application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The scanning electron microscope image and elemental energy spectrum analysis diagram of the AuAg-D nanoclusters before water absorption provided in Example 1 of the present application;

[0014] Figure 2 Mass spectra of AuAg-S nanocluster solutions at different laser powers provided in Example 1 of the present application;

[0015] Figure 3 The emission spectra of AuAg nanoclusters under 365nm light excitation and the corresponding CIE color coordinate diagram in different relative humidity environments provided in Example 1 of the present application;

[0016] Figure 4The absolute quantum efficiency test graphs of AuAg-D, AuAg-H and AuAg-S nanoclusters provided in Example 1 of the present application under 430, 410 and 410 nm light excitation respectively;

[0017] Figure 5 The peak fitting diagram of the emission spectrum of AuAg nanoclusters under 365nm light excitation in different relative humidity environments provided in Example 1 of the present application and the change diagram of the proportion of emitters I and II with relative humidity;

[0018] Figure 6 The variation trend and fitting diagram of the emission peak integrated intensity of AuAg nanoclusters under different excitation powers provided in Example 1 of the present application;

[0019] Figure 7 The fluorescence lifetime and fitting diagram of AuAg-D, AuAg-H and AuAg-S nanoclusters provided in Example 1 of the present application;

[0020] Figure 8 (a) Streak camera spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters under 400nm femtosecond laser excitation, (b) lifetime decay and fitting diagram at 480nm in the streak camera spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters provided in Example 1 of the present application

[0021] Fig. 9 (a) transient absorption spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters under 365nm femtosecond laser excitation provided in Example 1 of the present application, (b) lifetime decay and fitting diagrams of transient absorption spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters at monitoring wavelengths of 488 and 520nm, 480 and 490nm, 475 and 570nm, respectively;

[0022] Fig.10 The electron paramagnetic resonance spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters provided in Example 1 of the present application;

[0023] Fig.11 The Au L3 edge X-ray absorption near-edge structure spectra of (a) AuAg-D and (b) AuAg-H nanoclusters, and the Au L3 edge Fourier transform extended X-ray absorption fine structure spectra and fitting diagrams of (c) AuAg-D and (d) AuAg-H nanoclusters provided in Example 1 of the present application;

[0024] Fig.12 Fourier transform infrared spectra of AuAg-D and AuAg-H nanoclusters provided in Example 1 of the present application;

[0025] Fig.13 The emission spectra of the powder under 365nm excitation before and after water absorption of AuAg nanoclusters synthesized with different HAuCl4 and AgNO3 feed ratios provided in Example 2 of the present application;

[0026] Fig.14 Emission spectra of Au and AuCu nanocluster powders provided in Examples 3 and 4 of the present application under 365nm excitation;

[0027] Fig.15 The emission spectra of the AuAg nanoclusters synthesized at different solution pH values ​​provided in Example 5 of the present application before and after water absorption under 365nm excitation;

[0028] Fig.16 This is an emission spectrum diagram of the powder of AuAg nanoclusters synthesized with different zinc salts before and after water absorption under 365nm excitation provided in Example 6 of the present application. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] The present invention provides a method for preparing metal nanoclusters, comprising the following steps:

[0031] Adding a metal salt aqueous solution to ultrapure water, stirring evenly, then adding a 3-mercaptopropionic acid (MPA) solution and continuing to stir and react until precipitation is generated, adjusting the pH value of the solution to 7.70-8.40, then adding a zinc salt aqueous solution, and reacting under ultraviolet light irradiation to induce self-assembly of metal nanoclusters;

[0032] A zinc salt aqueous solution is added to the obtained metal nanoclusters for stirring reaction, and after centrifugation and discarding the supernatant, freeze-drying is performed. The freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds to obtain the obtained nanoclusters.

[0033] Wherein, the metal salt aqueous solution is a chloroauric acid (HAuCl4) aqueous solution or a mixture of a chloroauric acid aqueous solution and a silver nitrate aqueous solution or a copper chloride aqueous solution; preferably, the volume ratio of the chloroauric acid aqueous solution to the silver nitrate aqueous solution or the copper chloride aqueous solution is (0.64-0.76):(0.04-0.16).

[0034] The concentrations of the chloroauric acid aqueous solution, the silver nitrate aqueous solution, and the copper chloride aqueous solution are all 50 mM.

[0035] Preferably, the air humidity to which the metal nanoclusters are exposed is 60%, and the time for adsorbing water molecules in the air is 30 minutes.

[0036] Preferably, the molar mass ratio of MPA to HAuCl4 is 4:1.

[0037] Preferably, the pH value is 7.90.

[0038] Optionally, the zinc salt is one or more of Zn(OAc)2, ZnCl2, ZnBr2, ZnI2, Zn(ClO4)2, and Zn(CF3SO3)2.

[0039] Wherein, in the reaction under ultraviolet light irradiation conditions, the wavelength of the ultraviolet light is 365-410nm, and the reaction time is 18-30 hours, so as to promote the assembly process of metal nanoclusters and the formation of the structure.

[0040] Optionally, the step of adding a metal salt aqueous solution to ultrapure water, stirring evenly, adding a 3-mercaptopropionic acid solution, and continuing to stir and react until precipitation is generated, adjusting the pH value of the solution to 7.70-8.40, adding a zinc salt aqueous solution, and reacting under ultraviolet light irradiation to induce self-assembly of metal nanoclusters comprises:

[0041] In 9.2 mL of ultrapure water, add 0.64-0.76 mL of chloroauric acid aqueous solution and 0.04-0.16 mL of silver nitrate or copper chloride aqueous solution, and stir at room temperature to 600 rpm to ensure uniform distribution of metal ions, then add 138 μL of 3-mercaptopropionic acid (MPA) solution, and continue stirring until the solution changes from light yellow to white and precipitates. Among them, MPA molecules, as surface modifiers, can stabilize metal nanoclusters and provide active sites for reactions. In this step, MPA plays a role in stabilizing and protecting nanoclusters, and at the same time adjusts the pH of the reaction solution, so that AuAg NCs / AuCu NCs / Au NCs can exist stably.

[0042] The pH value of the solution is adjusted to 7.70-8.40 using 1M sodium hydroxide solution. Through this process, the precipitate gradually dissolves and the solution becomes transparent and colorless. For example, a AuAg NCs solution without photoluminescence is obtained, indicating that the metal ions have been successfully reduced to metal nanoclusters. 2mL of zinc salt aqueous solution is added to the solution, and the self-assembly treatment is carried out under 365-410nm ultraviolet light irradiation for 18-30 hours. The luminescent color of the solution is observed to change from no light to orange-red, indicating that the metal nanoclusters have begun to self-assemble. In this step, the addition of zinc salt is the key factor in triggering the self-assembly of AuAg NCs / AuCu NCs / Au NCs. In this step, zinc salt reacts with AuAg NCs / AuCu NCs / Au NCs to promote the self-assembly of their structures. The reaction is carried out at room temperature and lasts for 18-30 hours. As the reaction proceeds, the AuAg NCs / AuCu NCs / Au NCs undergo structural changes to form AuAg-S NCs / AuCu-S NCs / Au-S NCs, which emit bright sky blue light. The core of this process is the introduction of Zn on the surface of AuAg NCs / AuCu NCs / Au NCs. 2+ Ions promote their assembly to form stable nanostructures.

[0043] Optionally, the step of adding a zinc salt aqueous solution to the obtained metal nanoclusters for stirring reaction, centrifuging and discarding the supernatant, and then freeze-drying the metal nanoclusters, exposing the freeze-dried metal nanoclusters to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds, comprises:

[0044] After adding 2 mL of zinc salt aqueous solution to the obtained metal nanoclusters and stirring for 5 minutes, the mixture was centrifuged at 3000 rpm for 5 minutes, and the supernatant was discarded;

[0045] The obtained metal nanoclusters were solidified using liquid nitrogen and freeze-dried at -65 °C and 5 Pa for 3 days;

[0046] The freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds.

[0047] Specifically, in order to further improve the structure of AuAg NCs / AuCu NCs / Au NCs and fix its morphology, 2 mL of zinc salt aqueous solution was added to the AuAg-S NCs / AuCu-S NCs / Au-S NCs solution obtained in the above step. After mixing evenly, it was stirred for 5 minutes, and then the mixed solution was transferred to a centrifuge tube, centrifuged at a centrifugal force of 3000 rpm for 5 minutes, and the supernatant was discarded. The assembly of AuAg NCs / AuCu NCs / Au NCs was completely fixed by liquid nitrogen freezing treatment. The frozen AuAg NCs / AuCu NCs / Au NCs were freeze-dried at -65°C and 5 Pa in a vacuum environment for 3 days to obtain AuAg-DNCs / AuCu-DNCs / Au-D NCs. This step helps stabilize the luminescence properties by removing the solvent and fixing the structure of AuAg NCs / AuCu NCs / Au NCs under low temperature conditions and prepares for the subsequent passivation step.

[0048] Furthermore, in the AuAg-D NCs / AuCu-D NCs / Au-D NCs samples obtained in the above steps, due to the presence of structural oxygen vacancies, defective state emission exists. To solve this problem, these structural oxygen vacancies are passivated by the adsorption of water molecules in this step. The AuAg-D NCs / AuCu-D NCs / Au-DNCs are exposed to air so that they adsorb water molecules in the air. Water molecules bind to Au-O and Ag-O / Cu-O bonds through hydrogen bonds, which can effectively passivate these oxygen vacancies, thereby reducing the transfer of electrons from the ground state to the defect state. In this process, the adsorption of water molecules not only improves the photoluminescence quantum yield (PLQY) of AuAg NCs / AuCu NCs / Au NCs, but also changes the luminescent color from 536nm green emission to 480nm sky blue emission. In addition, water molecules interacted with the protective ligands through hydrogen bonding, further stabilizing the structure of AuAg NCs / AuCuNCs / Au NCs, making them more stable under light irradiation and reducing the nonradiative relaxation process, resulting in AuAg-H NCs / AuCu-H NCs / Au-HNCs with 480 nm sky blue emission.

[0049] Furthermore, after water molecules adsorbed and passivated structural defects, the photoluminescence performance of AuAg NCs / AuCu NCs / Au NCs was significantly improved. Through passivation treatment, the emission peak of AuAg NCs / AuCu NCs / Au NCs was continuously blue-shifted from 536nm to 480nm, and the luminescence quantum yield was increased from 5.3% to 91.6%. The successful implementation of this process not only demonstrates the important role of water molecules in improving the photoluminescence performance of nanoclusters, but also shows that this method can greatly improve the stability of luminescent materials. Ultimately, the obtained AuAg NCs have adjustable luminescence color and luminescence quantum efficiency at room temperature, and can be widely used in optoelectronics, display technology, sensors and other fields.

[0050] Among them, during the water adsorption process, the luminescence color of AuAg NCs / AuCu NCs / Au NCs changed from green to sky blue, indicating that the adsorption of water molecules has an impact on its luminescence properties. Water molecules interact with Au-O and Ag-O / Cu-O bonds through hydrogen bonds, effectively passivating the structural oxygen vacancies in the metal nanoclusters, inhibiting the defect state luminescence caused by structural oxygen vacancies, and accelerating the radiative luminescence rate of the intrinsic state. In addition, the addition of water molecules promotes the luminescence quantum efficiency of AuAgNCs / AuCu NCs / Au NCs by 15-20 times. Water molecules enhance the structural stability of metal nanoclusters through hydrogen bonds, inhibit non-radiative losses, and reduce the rate of electron-optical phonon coupling, thereby significantly improving the luminescence quantum efficiency of metal nanoclusters.

[0051] The synthesis method of the metal nanoclusters of the present application is simple and easy, and by precisely controlling the reaction conditions, it can maintain consistency and efficiency in large-scale production; the introduction of water molecules can not only effectively suppress the influence of oxygen vacancies, but also enhance the stability of the metal nanoclusters through hydrogen bonding, reduce non-radiative losses, and improve the overall optical performance. The metal nanoclusters obtained in the present application can significantly improve the luminous efficiency through the passivation of water molecules in a short time, thereby providing a new technical path for applications in different fields.

[0052] The embodiment of the present application also provides a metal nanocluster, which is prepared by the above-mentioned preparation method of the metal nanocluster. The metal nanocluster has a significantly improved luminescence quantum efficiency (PLQY), which is increased from 5.3% (defective state luminescence) to 91.6% (intrinsic state luminescence), and can achieve rapid adjustment of the luminescence color from 536nm to 480nm, and has fast and adjustable luminescence characteristics.

[0053] The metal nanoclusters provided in the embodiments of the present application can be suitable for applications such as optoelectronic devices, sensors, and photocatalysts, among which their excellent luminescence properties give them important application prospects in the above-mentioned fields.

[0054] The metal nanoclusters and the preparation methods thereof are described in detail with specific examples as follows. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.

[0055] Example 1: Synthesis of AuAg-H NCs

[0056] 1) Synthesis of AuAg nanoclusters: First, HAuCl4 aqueous solution (concentration of 50mM) and AgNO3 aqueous solution (concentration of 50mM) were added to ultrapure water at a molar ratio of 4:1. Solution 1 was obtained by stirring at room temperature. Then, 138uL 3-mercaptopropionic acid (MPA) was added to solution 1, and stirring was continued. A white precipitate was observed in the solution. Next, the pH value of the solution was adjusted to 7.90 by adding 1M NaOH solution, and the precipitate gradually dissolved to form a transparent solution, obtaining an AuAg NCs solution without luminescence properties.

[0057] 2) Self-assembly of AuAg-S nanoclusters: 2 mL of Zn(OAc)2 aqueous solution (concentration of 0.1 M) was added to the AuAg NCs solution obtained in step 1), and the reaction was carried out at room temperature for 24 hours to form AuAg-S NCs;

[0058] 3) Preparation of AuAg-D nanoclusters: In order to further improve the structure of AuAg NCs and fix its morphology, 2 mL of Zn(OAc)2 aqueous solution was added to the AuAg-S NCs solution obtained in step 2). After mixing evenly, stir for 5 minutes, then transfer the mixed solution to a centrifuge tube, centrifuge at 3000 rpm for 5 minutes, and discard the supernatant. The assembly of AuAg NCs was completely fixed by liquid nitrogen freezing. The frozen AuAg NCs were freeze-dried at -65°C and 5 Pa in a vacuum environment for 3 days to obtain AuAg-D NCs.

[0059] 4) Water molecule passivation treatment of AuAg-D nanoclusters: The AuAg-D NCs sample obtained in step 3) was exposed to the air to adsorb water molecules in the air. The water molecules bonded to the Au-O and Ag-O bonds, passivated the structural oxygen vacancies, and prevented the electron transfer from the cluster eigenstate to the defect state, making the cluster eigenstate the main channel for radiative relaxation, and obtaining AuAg-H NCs with 480nm sky blue emission.

[0060] 5) Regulation of luminescent color and luminescent efficiency: After water molecules adsorb and passivate structural defects, the photoluminescence performance of AuAg NCs is significantly improved. Through passivation treatment, the emission peak of AuAg NCs is continuously blue-shifted from 536nm to 480nm, and the luminescent quantum yield is increased from 5.3% to 91.6%.

[0061] like Figure 1 As shown, scanning electron microscopy (SEM) images reveal that the unique water absorption properties of AuAg-D nanoclusters are driven by their intrinsic porous microstructure.

[0062] like Figure 2 As shown, the positive ion mode matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry of the AuAg-S nanoclusters showed that their composition was Au8Ag2(MPA)6.

[0063] like Figure 3 As shown in the figure, under 365nm light excitation, AuAg-D nanoclusters exhibit a green emission peak of 536nm. The continuous absorption of water molecules by AuAg-D nanoclusters will continuously blue-shift its emission band and significantly enhance the emission intensity. Therefore, the final AuAg-S nanoclusters exhibit a sky-blue emission of 480nm. Correspondingly, the International Commission on Illumination (CIE) chromaticity coordinates of AuAg nanoclusters can be adjusted in a wide range, from (0.23, 0.67) of AuAg-D nanoclusters to (0.10, 0.17) of AuAg-S nanoclusters.

[0064] like Figure 4 As shown, under the excitation of band edge energy, the absolute photoluminescence quantum yields of AuAg-D, AuAg-H and AuAg-S nanoclusters were determined to be 5.3%, 79.5% and 91.6%, respectively.

[0065] like Figure 5 As shown in the figure, the Gaussian fitting of the emission peaks of AuAg-D and AuAg-D nanoclusters under different relative humidity environments found that emitters Ⅰ (2.55 eV) and Ⅱ (about 2.42 eV) can be fitted. In addition, as the relative humidity (RH) conditions increase, the proportion of emitter Ⅰ increases, while the proportion of emitter Ⅱ decreases, which indicates that water molecules can change the radiation channel in AuAg nanoclusters.

[0066] like Figure 6As shown in the figure, the excitation power-dependent photoluminescence spectra of AuAg-D, AuAg-H and AuAg-S nanoclusters were measured under 350nm pulsed laser pumping and the data were fitted. The k values ​​obtained from the fitting results of the corresponding AuAg-D, AuAg-H and AuAg-S nanoclusters were 0.439, 0.966 and 0.974, respectively, proving that emitter I in all AuAg nanoclusters is the cluster intrinsic state emission center, while emitter II belongs to the defect state emission center.

[0067] like Figure 7 As shown in Figure 2, three time components are extracted from the luminescence decay of AuAg-D nanoclusters, namely 16.9 ns (τ1, 56%), 302.4 ns (τ2, 21%), and 4241.4 ns (τ3, 23%). The average PL lifetime (τ ave ) is 1048.5 ns. However, for the luminescence decay of AuAg-H nanoclusters, only two time components can be fitted, namely 29.5 ns (τ1, 73%) and 72.8 ns (τ2, 27%). ave The value is 41.6 nanoseconds. In addition, the luminescence decay of AuAg-S nanoclusters exhibits a single exponential radiative decay with a time of 69.5 nanoseconds. τ1 and τ2 are attributed to the non-radiative and radiative relaxation of excitons in AuAg nanoclusters, respectively. In addition, it should be noted that the τ1 and τ2 in the luminescence lifetime of AuAg-D nanoclusters indicate that its defect state emission originates from the electron transfer of the eigenstate of AuAg nanoclusters.

[0068] like Figure 8 As shown in the figure, the luminescence band at 480 nm was detected in the streak camera images of all AuAg nanoclusters, while the defect state emission at 536 nm was only detected in AuAg-D and AuAg-H nanoclusters. The lifetime fitting of the luminescence decay at 480 nm in the three nanoclusters shows that only the AuAg-S nanocluster contains a single decay component (>1ns), which corresponds to the radiative relaxation of the intrinsic emission state of the AuAg nanocluster. The luminescence decay of the AuAg-D and AuAg-H nanoclusters contains an ultrafast decay component (32.9ps and 78.5ps, respectively) and a radiative relaxation component (>1ns). Therefore, 32.9ps and 78.5ps belong to the electron transfer process in the AuAg-D and AuAg-H nanoclusters, respectively. Therefore, the introduced H2O molecules can suppress the electron transfer process from the intrinsic emission state of the AuAg nanocluster to the defect emission state.

[0069] like Fig. 9As shown, the ESA kinetic fitting results of the AuAg-D nanoclusters at 488nm and 520nm show two decay time components: 29.1 nanoseconds and >1 nanosecond, corresponding to the electron injection process and the radiative relaxation of excited electrons in the defect state, respectively. In addition, the ESA kinetic fitting results of the AuAg-H nanoclusters at 480nm and 490nm show three decay components: 6.8 picoseconds, 81.3 picoseconds and >1 nanosecond, corresponding to the structural relaxation (SR) in the S1 sublevel, the electron transfer process from the native AuAg nanocluster luminescent state to the defect luminescent state, and the radiative relaxation of excited electrons in the S1 state in the AuAg nanoclusters, respectively. Finally, the ESA kinetic fitting results of the AuAg-S nanoclusters at 475nm and 570nm also show three decay components: 0.9 picoseconds, 8.5 picoseconds and >1 nanosecond, corresponding to the hot electrons from the S n The internal conversion from the S1 state to the S1 state, the structural relaxation process and the radiative relaxation process. The water molecules initially adsorbed in the AuAg-H nanoclusters significantly slowed down the electron transfer process and transformed the emission from the defect state to the intrinsic state emission of the AuAg nanoclusters. The continuously adsorbed water molecules completely suppressed the electron transfer process in the AuAg-S nanoclusters and suppressed the non-radiative structural relaxation, which ultimately led to the enhanced luminescence of the AuAg nanoclusters.

[0070] like Fig.10 As shown in Figure 3, the EPR spectrum of the AuAg-D nanocluster shows a significant EPR signal at g = 2.003, which is attributed to the oxygen vacancy defect near the metal atom in the AuAg nanocluster. The intensity of the defect signal gradually weakens from the AuAg-D nanocluster, indicating that water molecules can effectively passivate the oxygen vacancy defect.

[0071] like Fig.11 As shown in Figure 3, the data fitting of the X-ray absorption near-edge structure spectra of AuAg-D and AuAg-H nanoclusters at the Au L3 edge and Ag K edge showed that there were no Au-O and Ag-O paths in the Au L3 edge and Ag K edge FT-EXAFS fitting of AuAg-D nanoclusters, while these paths existed in AuAg-H nanoclusters, which further confirmed that the adsorbed water molecules can generate Au-O and Ag-O bonds, thereby passivating oxygen vacancy defects.

[0072] like Fig.12 As shown in the FTIR spectra of AuAg-D and AuAg-H nanoclusters, the stretching vibration of the -C=O group in the AuAg-D and AuAg-H nanoclusters undergoes a significant red shift, indicating that a hydrogen bond is formed between the water molecules and the -C=O group in the MPA ligand. In addition, the -C=O group in the AuAg-D nanoclusters at 2933 cm -1 The methylene stretching vibration peaks in AuAg-H nanoclusters are split into 2987, 2962, 2934, and 2913 cm-1 The sub-peak of is attributed to the vibrational coupling of adjacent methylene groups in the MPA ligand induced by the newly formed hydrogen bonds.

[0073] In summary, the preparation method of metal nanoclusters proposed in this application can regulate the luminescence properties of metal nanoclusters. The adsorbed water molecules in the AuAg nanoclusters can blue-shift the luminescence peak from 536nm to 480nm, and significantly increase the absolute photoluminescence quantum yield from 5.3% to 91.6%. The green PL of 536nm in the AuAg-D nanocluster was proved to be the slow radiation defect state emission of the oxygen vacancy center, which originated from the electron transfer from the intrinsic emission state of the AuAg nanocluster. Water molecules can anchor them to the exposed Au and Ag atoms in the metal core by forming Au-O and Ag-O bonds. The passivation of oxygen vacancy defects by water molecules inhibits the electron transfer process and transforms the fast-radiating intrinsic emission state of the AuAg nanocluster into the main luminescence path. Excess adsorbed water molecules also help stabilize the AuAg nanoclusters and suppress the intensity and energy of non-radiative electron-optical phonon coupling. Finally, an ultra-high absolute luminescence quantum efficiency of 91.6% was achieved in AuAg-S nanoclusters.

[0074] Example 2: Synthesis of AuAg nanoclusters with different HAuCl4 and AgNO3 feed ratios

[0075] This embodiment is similar to the above embodiment 1, except that step 1):

[0076] 1) Synthesis of AuAg nanoclusters: In 9.2 mL of ultrapure water, add 0.64-0.76 mL of HAuCl4 (50 mM) and 0.04-0.16 mL of AgNO3 (50 mM) aqueous solution, and stir at 600 rpm at room temperature to ensure uniform distribution of metal ions. Then add 138 μL of 3-mercaptopropionic acid (MPA) solution, and continue stirring until the solution changes from light yellow to white and a precipitate is produced. Then, the pH value of the solution is adjusted to 7.90 by adding 1 M NaOH solution, and the precipitate gradually dissolves to form a transparent solution, obtaining an AuAg NCs solution without luminescent properties.

[0077] Fig.13 The emission spectra of the powder under 365nm excitation before and after water absorption of AuAg nanoclusters synthesized with different HAuCl4 and AgNO3 feed ratios are shown.

[0078] Example 3: Synthesis of Au-H NCs

[0079] 1) Synthesis of Au nanoclusters: In 9.2 mL of ultrapure water, add 0.8 mL of HAuCl4 (50 mM) aqueous solution and stir at 600 rpm at room temperature to ensure uniform distribution of metal ions. Then add 138 μL of 3-mercaptopropionic acid (MPA) solution and continue stirring until the solution changes from light yellow to white and a precipitate is produced. Next, adjust the pH value of the solution to 7.90 by adding 1 M NaOH solution, the precipitate gradually dissolves and forms a transparent solution, and obtains an Au NCs solution without luminescence properties.

[0080] 2) Self-assembly of Au-S nanoclusters: 2 mL of Zn(OAc)2 aqueous solution (concentration of 0.1 M) was added to the Au NCs solution obtained in step 1), and the reaction was carried out at room temperature for 24 hours to form Au-S NCs;

[0081] 3) Preparation of Au-D nanoclusters: In order to further improve the structure of Au NCs and fix its morphology, 2 mL of Zn(OAc)2 aqueous solution was added to the Au-S NCs solution obtained in step 2). After mixing evenly, stir for 5 minutes, then transfer the mixed solution to a centrifuge tube, centrifuge at 3000 rpm for 5 minutes, and discard the supernatant. The assembly of Au NCs was completely fixed by liquid nitrogen freezing. The frozen Au NCs were freeze-dried at -65°C and 5 Pa in a vacuum environment for 3 days to obtain Au-D NCs.

[0082] 4) Water molecule passivation treatment of Au-D nanoclusters: The Au-D NCs sample obtained in step 3) was exposed to an environment with a relative humidity of 56% to allow it to adsorb water molecules in the air for 30 minutes. The water molecules bonded to the Au-O bonds, passivated the structural oxygen vacancies, and prevented the electron transfer from the cluster eigenstate to the defect state, making the cluster eigenstate the main channel for radiative relaxation, and obtaining Au-H NCs with a sky blue emission of 480nm.

[0083] Example 4: Synthesis of AuCu-H NCs

[0084] 1) Synthesis of AuCu nanoclusters: In 9.2 mL of ultrapure water, add 0.67 mL of HAuCl4 (50 mM) and 0.13 mL of CuCl2 (50 mM) aqueous solution and stir at 600 rpm at room temperature to ensure uniform distribution of metal ions. Then add 138 μL of 3-mercaptopropionic acid (MPA) solution and continue stirring until the solution changes from light yellow to white and a precipitate is produced. Next, adjust the pH value of the solution to 7.90 by adding 1 M NaOH solution, the precipitate gradually dissolves and forms a transparent solution, and obtains an AuCu NCs solution without luminescence properties.

[0085] 2) Self-assembly of AuCu-S nanoclusters: 2 mL of Zn(OAc)2 aqueous solution (concentration of 0.1 M) was added to the AuCu NCs solution obtained in step 1), and the reaction was carried out at room temperature for 24 hours to form AuCu-S NCs;

[0086] 3) Preparation of AuCu-D nanoclusters: In order to further improve the structure of AuCu NCs and fix its morphology, 2 mL of Zn(OAc)2 aqueous solution was added to the AuCu-S NCs solution obtained in step 2). After mixing evenly, stir for 5 minutes, then transfer the mixed solution to a centrifuge tube, centrifuge at 3000 rpm for 5 minutes, and discard the supernatant. The assembly of AuCu NCs was completely fixed by liquid nitrogen freezing. The frozen AuCu NCs were freeze-dried at -65°C and 5 Pa in a vacuum environment for 3 days to obtain AuCu-D NCs.

[0087] 4) Water molecule passivation treatment of AuCu-D nanoclusters: The AuCu-D NCs sample obtained in step 3) was exposed to an environment with a relative humidity of 56% to allow it to adsorb water molecules in the air for 30 minutes. The water molecules bonded to the Au-O and Cu-O bonds, passivating the structural oxygen vacancies and preventing the electron transfer from the cluster eigenstate to the defect state, making the cluster eigenstate the main channel for radiative relaxation, and obtaining AuCu-H NCs with a sky blue emission of 480nm.

[0088] Fig.14 The emission spectra of Au and AuCu nanocluster powders under 365 nm excitation are shown.

[0089] Example 5: Synthesis of AuAg nanoclusters at different solution pH values

[0090] This embodiment is similar to the above embodiment 1, except that step 1):

[0091] 1) Synthesis of AuAg nanoclusters: In 9.2 mL of ultrapure water, add 0.67 mL of HAuCl4 (50 mM) and 0.13 mL of AgNO3 (50 mM) aqueous solution, and stir at 600 rpm at room temperature to ensure uniform distribution of metal ions. Then add 138 μL of 3-mercaptopropionic acid (MPA) solution, and continue stirring until the solution changes from light yellow to white and a precipitate is produced. Then, the pH value of the solution is adjusted to 7.70-8.40 by adding 1 M NaOH solution, and the precipitate gradually dissolves to form a transparent solution, obtaining an AuAg NCs solution without luminescent properties.

[0092] Fig.15The emission spectra of the powder under 365nm excitation before and after water absorption of AuAg nanoclusters synthesized at different solution pH values ​​are shown.

[0093] Example 6: Synthesis of AuAg nanoclusters from different zinc salts

[0094] This embodiment is similar to the above-mentioned embodiment 1, except that the zinc salt is replaced by Zn(OAc)2, ZnCl2, ZnBr2, ZnI2, Zn(ClO4)2, and Zn(CF3SO3)2, respectively.

[0095] Fig.16 The emission spectra of the powders under 365nm excitation before and after water absorption of AuAg nanoclusters synthesized with different zinc salts are shown.

[0096] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0097] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing metal nanoclusters, characterized in that: include: Adding a metal salt aqueous solution to ultrapure water, stirring evenly, then adding a 3-mercaptopropionic acid solution and continuing to stir and react until precipitation is generated, adjusting the pH value of the solution to 7.70-8.40, then adding a zinc salt aqueous solution, and reacting under ultraviolet light irradiation to induce self-assembly of metal nanoclusters; A zinc salt aqueous solution is added to the obtained metal nanoclusters for stirring reaction, and after centrifugation and discarding the supernatant, freeze-drying is performed, and the freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds, thereby obtaining; Wherein, the metal salt aqueous solution is a chloroauric acid aqueous solution or a mixture of a chloroauric acid aqueous solution and a silver nitrate aqueous solution or a cupric chloride aqueous solution.

2. The method for preparing metal nanoclusters according to claim 1, characterized in that: The zinc salt is one or more of Zn(OAc)2, ZnCl2, ZnBr2, ZnI2, Zn(ClO4)2, and Zn(CF3SO3)2.

3. The method for preparing metal nanoclusters according to claim 1, characterized in that: In the reaction under ultraviolet light irradiation, the wavelength of the ultraviolet light is 365-410nm and the reaction time is 18-30 hours.

4. The method for preparing metal nanoclusters according to claim 1, characterized in that: The volume ratio of the chloroauric acid aqueous solution to the silver nitrate aqueous solution or the copper chloride aqueous solution is (0.64-0.76):(0.04-0.16).

5. The method for preparing metal nanoclusters according to claim 4, characterized in that: The concentrations of the chloroauric acid aqueous solution, the silver nitrate aqueous solution, and the copper chloride aqueous solution are all 50 mM.

6. The method for preparing metal nanoclusters according to claim 1, characterized in that: The method comprises adding a metal salt aqueous solution to ultrapure water, stirring evenly, adding a 3-mercaptopropionic acid solution, and continuing to stir and react until precipitation is generated, adjusting the pH value of the solution to 7.70-8.40, adding a zinc salt aqueous solution, and reacting under ultraviolet light irradiation to induce self-assembly of metal nanoclusters, including: In 9.2 mL of ultrapure water, add 0.64-0.76 mL of chloroauric acid aqueous solution and 0.04-0.16 mL of silver nitrate or copper chloride aqueous solution, and stir at 600 rpm at room temperature to ensure uniform distribution of metal ions, then add 138 μL of 3-mercaptopropionic acid solution, and continue stirring until the solution changes from light yellow to white and precipitates; The pH value of the solution was adjusted to 7.70-8.40 using 1 M sodium hydroxide solution, 2 mL of an aqueous zinc salt solution was added to the solution, and the solution was reacted under 365-410 nm ultraviolet light irradiation conditions to induce self-assembly of metal nanoclusters.

7. The method for preparing metal nanoclusters according to claim 6, characterized in that: The method comprises adding a zinc salt aqueous solution to the obtained metal nanoclusters for stirring reaction, centrifuging and discarding the supernatant, and then freeze-drying the metal nanoclusters. The freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds, including: After adding 2 mL of zinc salt aqueous solution to the obtained metal nanoclusters and stirring for 5 minutes, the mixture was centrifuged at 3000 rpm for 5 minutes, and the supernatant was discarded; The obtained metal nanoclusters were solidified using liquid nitrogen and freeze-dried at -65 °C and 5 Pa for 3 days; The freeze-dried metal nanoclusters are exposed to an environment with a relative humidity of not less than 2% so that water molecules interact with metal oxygen bonds through hydrogen bonds.

8. A metal nanocluster, characterized in that: The metal nanoclusters are prepared by the method for preparing metal nanoclusters according to any one of claims 1 to 7.

9. The metal nanocluster according to claim 8, characterized in that: The luminescence quantum efficiency of the metal nanoclusters is increased from 5.3% to 91.6%, and the luminescence color can be adjusted within milliseconds, and can be quickly adjusted from 536nm to 480nm.

10. Use of the metal nanoclusters according to claim 8 in the fields of optoelectronic devices, sensors and photocatalysts.

Citation Information

Patent Citations

  • Nanogold solution and method for detecting Co<2+> by using same

    CN102416482A

  • Method of manufacturing fluorescent gold nanoclusters with improved quantum yield and fluorescent gold nanoclusters manufactured thereby

    KR1020180086754A

  • Preparation method for ratio fluorescent lactic acid probe based on novel nanocomposite system and enzyme catalytic reaction

    WO2021223317A1